INTERNATIONAL EXPERIENCE OF USING AI IN TEACHING ENGLISH - Tsyntar, Natalia (Learning & Teaching: in the World after War: Conference Proceedings of III International Scientific & Practical Conference, Kharkiv, Ukraine, 2024)
As the global language of communication, English is one of the most used languages for jobs, markets, tourism, discourse, and international interaction. As While English is a highly desirable language to attain, there are a number of obstacles for learners to overcome such as insufficient input to the target language, limited opportunities for using English inside and outside the classroom etc. Artificial intelligence (AI) is being used as a tool to support English language teaching and learning (ELT/L) that can provide new strategies and opportunities to overcome challenges and enhance learning of a foreign language.
Keywords: Artificial intelligence, different educational levels, data privacy regulations, advanced technologies